ANÁLISIS A LOS ESTADOS FINANCIEROS Y PROPUESTA DE MEJORAS A LA COOPERATIVA DE AHORRO Y CRÉDITO CATAMAYO LTDA. PERIODO 2016-2017 - Auquilla Yangua, Andrea Alejandra (2019)
The present thesis work was carried out in order to know the most significant financial variations in the Savings and Credit Cooperative Catamayo in the periods 2016-2017. As well as the levels of liquidity, profitability, indebtedness and growth of the cooperative, and in relation to these results to elaborate improvement proposals that contribute to the financial entity. The work was developed based on the identification of the financial problems of the Savings and Credit Cooperative Catamayo Ltda. Period 2016-2017 ", for which it is investigated in bibliographical sources for the theoretical sustenance of the investigation, applying the inductive and deductive methods in the development of vertical and horizontal analysis. The same ones that allowed observing that in the General Balance there was an increase of the asset in relation to the credit portfolio, as well as in the liabilities with obligations to the public. Likewise, in the Balance of Results the income and expenses of the cooperative increased in the same proportion. Likewise, in the application of the indicators of the Pearl Monitoring System to the financial statements of the entity they helped to know that the cooperative does not comply with the established goals, such as provisions for loans higher and lower than twelve months; and in its financial structure of the patrimony it does not have a strong net institutional capital. The information obtained is presented in tables and graphs with their respective analysis. Based on the results obtained, the respective conclusions and recommendations have been elaborated in function of the study objectives, as well as the proposal that leads to provide base strategies that will be directed to the benefit and development of the cooperative.